Project characteristics for design and build procurement in Malaysian construction industry - Gambo, M. M. (Malaysian Technical Universities Network (MTUN), 2015)
Design & Build procurement approach is one of the procurement methods which is known to be widely gaining popularity in order to serve the modern day construction clients desire of having a constructed facility. To effectively service the market-driven expansion of this project delivery strategy in the construction community, a fundamental understanding of the characteristics of the Design & Build procurement approach is necessary. This study is aimed at appraising the Design & Build procurement approach in the Malaysian construction industry based on current practice through identifying the characteristics of the procurement approach. For this purpose, a detailed literature review of the Design & Build characteristics was conducted and data was collected from a two round Delphi questionnaire survey conducted with experienced professionals that have vast experience in the Design & Build procurement practice. The relative importance of these characteristics were quantified by the relative importance index method demonstrating their level of priority. The key findings in the study showed that the practice of the procurement approach in Malaysia is most importantly characterized by the fact that it is most suitable for projects that are complex in nature, while ‘effective client representation’ is the least important characteristic of the Design & Build procurement approach with regard to the Malaysian construction industry. It is expected that with the consideration of these characteristics of the D&B procurement approach, it will consequently result in the overall improvement in the performance of the Malaysian construction industry in relation to project delivery.